The Effectiveness of Using Video Modeling based on Distance Learning in Developing the Skills of Creating Digital Content among Students of the Faculty of Education According to their Training Needs - Rania Abed Moneim (دراسات: العلوم التربوية, 2021)
The research aims to employ distance learning-based- video modeling in developing the skills of making digital content for the students of the Education College according to their training needs. The quasi-experimental approach was applied, and a purposive research sample consisting of (52) students from the College of Education at Al-Aqsa University was selected. The research tools were (scale of needs, cognitive test, educational product card) to develop digital content production skills. The results of the research revealed that students are in bad need of training in producing digital content. Based on these results the experiment was conducted and the results revealed a statistically significant difference in the two scales in favor of post-implementation and gain ratio (1.22). This confirms the effectiveness and efficiency of distance learning-based- video modeling in developing the skills of making digital content for the students of the Faculty of Education at Al-Aqsa University in Gaza.